2011
DOI: 10.1152/ajpregu.00289.2011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro insulin and fasting control of the transmembrane fatty acid transport proteins in Atlantic salmon (Salmo salar)

Abstract: (FABP3), and mitochondrial FA-CoA and -carnitine palmitoyl transferase carriers (CPT)1 and -2 in Atlantic salmon tissues and myocyte cell culture. Two weeks of fasting diminished FATP1, CD36, and LPL in adipose tissue, suggesting a reduction in FA uptake, while FABP3 increased in liver, probably enhancing the transport of FA to the mitochondria. Insulin injection decreased FATP1 and CD36 in white and red muscles, while both transporters were upregulated in the adipose tissue in agreement with the role of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
2
19
1
Order By: Relevance
“…In liver, insulin treatment resulted in decreased concentration of FA, triglyceride, glucose, and glycogen, and increased mRNA abundance of FAT/CD36, FAS, PPARa, and SREBP1c. These changes are in agreement with those previously observed in vivo in the same [27][28][29]33,45] and other fish species [20,46] after insulin treatment. Moreover, other variables that had not been assessed in comparable studies in fish liver before, such as decreased mRNA abundance of UCP2a or SUR-like are indicative of decreased mitochondrial activity elicited by insulin treatment.…”
Section: Effects Of Treatment With Fa or Insulin Alonesupporting
confidence: 93%
“…In liver, insulin treatment resulted in decreased concentration of FA, triglyceride, glucose, and glycogen, and increased mRNA abundance of FAT/CD36, FAS, PPARa, and SREBP1c. These changes are in agreement with those previously observed in vivo in the same [27][28][29]33,45] and other fish species [20,46] after insulin treatment. Moreover, other variables that had not been assessed in comparable studies in fish liver before, such as decreased mRNA abundance of UCP2a or SUR-like are indicative of decreased mitochondrial activity elicited by insulin treatment.…”
Section: Effects Of Treatment With Fa or Insulin Alonesupporting
confidence: 93%
“…Even though we cannot eliminate a putative difference linked to the generation of selection (5th vs. 3rd and 4th), these discrepancies could be due to the nutritional status of the fish, because this is the first time that we analyzed fasted fish (48 h prior to the peritoneal injection). Indeed, unfed fish use fatty acids as the preferential energy source [60] in contrast to fed fish; we can hypothesize that fatty acid potential could be strongly changed in this context in the fish lines.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of fish FATPs also remains greatly unexplored. Only recently, few studies have been reported on the regulation of FATPs expression in Atlantic salmon and rainbow trout (S anchez-Gurmaches, Cruz-Garcia, Guti errez & Navarro, 2012;S anchez-Gurmaches et al, 2011;Todor cevi c et al, 2008;Torstensen, Nanton, Olsvik, Sundvold & Stubhaug, 2009). It has been suggested that insulin, fasting, and inflammation and infection mediators could regulate the gene expression of fish FATP1.…”
Section: Tissue Distribution Of Fatps In Japanese Seabassmentioning
confidence: 99%